2020
DOI: 10.3390/ijerph17228399
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Characteristics Associated with Older Adults’ Social Participation: The Contribution of Sociodemography and Transportation in Metropolitan, Urban, and Rural Areas

Abstract: Although social participation fosters older adults’ health, little is known about which environmental characteristics are related to greater participation in social activities. The Canadian Community Health Survey (n = 2737), a transportation survey, and multiple secondary data sources were used to identify the environmental characteristics associated with older Quebecers’ social participation according to living area. Greater social participation was associated with: (1) a higher concentration of older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(67 reference statements)
1
19
0
1
Order By: Relevance
“…A better understanding of the residential characteristics that influence social participation is lacking. Levasseur et al (2020) found that greater social participation was linked to an older population concentration in large metropolitan and rural areas, but not in urban areas [27]. In China, urban-rural differences should be researched from a hierarchical perspective; the differences between cities, towns, and rural areas show variations in social culture and geographical characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A better understanding of the residential characteristics that influence social participation is lacking. Levasseur et al (2020) found that greater social participation was linked to an older population concentration in large metropolitan and rural areas, but not in urban areas [27]. In China, urban-rural differences should be researched from a hierarchical perspective; the differences between cities, towns, and rural areas show variations in social culture and geographical characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Québec and Canada, public health studies and surveys indicate that this pandemic has had significant personal implications, not to mention social and financial impacts. On the individual level, studies report a decrease in sleep time, and an increase in psychological distress, stress and anxiety, depressive symptoms, suicidal ideation, and alcohol and cannabis use (Best et al, 2020 ; Dozois & Mental Health Research Canada, 2020 ; Généreux et al, 2020 ; INSPQ, 2020 ; Robillard et al, 2020 ). On the social level, there has been an increase in contact with immediate family members, but a decrease in contact with friends and in the quality of relationships with family and friends (Robillard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rural contexts, older people do not have multiple public transportation systems [ 22 ]. To use public transportation systems, they must wait for a long time or walk to stations far from their houses; this can prevent them from shopping [ 23 ]. Therefore, their families often support their shopping or buy their utilities [ 24 ].…”
Section: Discussionmentioning
confidence: 99%